2004
DOI: 10.1016/j.jasms.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase reactions of divalent Ni complex ions with acetonitrile: Chelate ring size, inductive, and steric effects

Abstract: Ni(II) complexes of a series of pentadentate polyamine ligands have been reacted with CH 3 CN in the gas phase using a modified quadrupole ion trap mass spectrometer. The ligands have structural features such that upon complexation, chelate ring size, sterics, and inductive effects can be evaluated in the gas phase. Rate and equilibrium constants for CH 3 CN addition to the metal complexes show that there is a general decrease in the gas-phase reactivity as the chelate ring size is increased. Density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…So it can be concluded that faster reaction was observed with larger chelating ligand size. This conclusion is supported by Combariza and Vachet [38], where they report that in solution when chelating ring size increases from 5 to 7 a substantial increase of stability is observed in gas phase while the converse is true in solution where poorer metal-ligand overlap is observed as ligand size increase.…”
Section: Resultsmentioning
confidence: 69%
“…So it can be concluded that faster reaction was observed with larger chelating ligand size. This conclusion is supported by Combariza and Vachet [38], where they report that in solution when chelating ring size increases from 5 to 7 a substantial increase of stability is observed in gas phase while the converse is true in solution where poorer metal-ligand overlap is observed as ligand size increase.…”
Section: Resultsmentioning
confidence: 69%
“…14 on the two position of each pyridine ring (Fig. 15), but the extent of reaction is noticeably different in each case [65]. Steric hindrance by the methyl group circled in Fig.…”
Section: The Effect Of Steric Interactionsmentioning
confidence: 96%
“…A formação destes complexos foi atribuída previamente à cavidade do éter, a qual determina a estequiometria do complexo em solução 29 . Atualmente, o emprego dos éteres de coroa não se limita à coordenação com cátions metálicos, mas também no estudo das constantes de estabilidade 31 34 . Devido a este fato, estudos de estabilidade e labilidade de ambos complexos formados (metal:solvente ou metal:agente quelante) devem ser levados em consideração 34 .…”
Section: +unclassified
“…Atualmente, o emprego dos éteres de coroa não se limita à coordenação com cátions metálicos, mas também no estudo das constantes de estabilidade 31 34 . Devido a este fato, estudos de estabilidade e labilidade de ambos complexos formados (metal:solvente ou metal:agente quelante) devem ser levados em consideração 34 . Um dos problemas que limitam o uso de competidores do tipo éter de coroa e seus derivados é a quantidade necessária para deslocar o equilíbrio da formação da molécula cationizada para a molécula protonada.…”
Section: +unclassified